2022
DOI: 10.1158/1078-0432.ccr-21-3716
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Analysis of Cell-free Circulating Tumor DNA is Suitable for Early Relapse and Actionable Target Detection in Patients with Neuroblastoma

Abstract: Purpose: Treating refractory or relapsed neuroblastoma remains challenging. Monitoring body fluids for tumor-derived molecular information indicating minimal residual disease supports more frequent diagnostic surveillance and may have the power to detect resistant subclones before they give rise to relapses. If actionable targets are identified from liquid biopsies, targeted treatment options can be considered earlier. Experimental Design: … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 50 publications
2
27
1
Order By: Relevance
“…Establishing the clinical applicability of plasma-based liquid biopsies in pediatric cancer patients versus adult patients has been challenging due to the limited sample volumes from infants and young children, small cohort sizes for individual tumor types, as well as the varied nature of the genomic alterations that characterize pediatric solid tumors. Nevertheless, several studies have described the feasibility of NGS-based approaches in pediatric solid tumors 19 , 21 – 24 , 30 , 31 , 35 37 . For example, to detect neuroblastoma-specific markers for LB biobanking strategies in 84 infants, Lodrini et al showed that as little as 1–2 ml of blood plasma, CSF, or urine had sufficient cfDNA for disease monitoring and ultimately clinical implementation of LB assays 23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Establishing the clinical applicability of plasma-based liquid biopsies in pediatric cancer patients versus adult patients has been challenging due to the limited sample volumes from infants and young children, small cohort sizes for individual tumor types, as well as the varied nature of the genomic alterations that characterize pediatric solid tumors. Nevertheless, several studies have described the feasibility of NGS-based approaches in pediatric solid tumors 19 , 21 – 24 , 30 , 31 , 35 37 . For example, to detect neuroblastoma-specific markers for LB biobanking strategies in 84 infants, Lodrini et al showed that as little as 1–2 ml of blood plasma, CSF, or urine had sufficient cfDNA for disease monitoring and ultimately clinical implementation of LB assays 23 .…”
Section: Discussionmentioning
confidence: 99%
“…The feasibility of employing NGS and droplet digital PCR-based assays utilizing cfDNA derived from CSF, plasma, or the aqueous humor of the eye for pediatric central nervous system (CNS) tumors, solid tumors, or retinoblastoma, respectively, has recently been described 10 , 19 27 . In the diagnostic setting, ultra-low-pass WGS (ULP-WGS) analysis of plasma ctDNA was effectively used to distinguish malignant peripheral nerve sheath tumors (MPNST) from the benign lesion, plexiform neurofibroma (PN), in patients with the neurofibromatosis type 1 (NF1) cancer predisposition syndrome 28 .…”
Section: Introductionmentioning
confidence: 99%
“…The presence of neuroblastoma-specific mRNA in the cellular compartment of blood and bone marrow, such as PHOX2B , TH and CHRNA3 , has been shown to correlate with outcome, enabling response monitoring in patients with high-risk disease [ 6 , 7 , 8 , 9 ]. Additionally, several targets in cell-free DNA (cfDNA) from plasma have been described to track therapy response, disappearing as tumor burden decreases and re-appearing as the disease relapses [ 10 , 11 , 12 , 13 ]. However, the presence of tumor-specific mRNA is often attributed to circulating tumor cells, which are not always present in every stage of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of the methylated tumor suppressor gene RASSF1A can be detected in plasma for several types of pediatric solid tumors, and can be used to monitor therapy response ( 25 , 26 ). For neuroblastoma, tumor-specific aberrations in the MYCN and ALK genes (mutations and copy number alterations) can be monitored during the course of the disease ( 27 , 28 ). Copy number profiling can be performed on cell-free DNA to detect a tumor-derived signal, and this can be combined with the copy number profile from the primary tumor, offering a more comprehensive overview of the genetic landscape of the tumor and its metastatic lesions ( 29 ).…”
Section: Introductionmentioning
confidence: 99%